(untitled) (Iranian Journal of Kidney Diseases, 2024)
Non-albuminuric diabetic kidney disease (NA-DKD) is characterized by progressive loss of kidney function with an annual loss of estimated glomerular filtration rate (eGFR) more than 3 mL/ min/ 1.73m2 per year. NA-DKD is also associated with the late manifestation of diabetic kidney disease, characterized by reduced eGFR (< 60 mL/min/ 1.73m2), in the absence of albuminuria (urine albumin-to-creatinine ratio [UACR] less than 30 mg/g. The typical glomerular changes seen in diabetic nephropathy are less frequently observed in normoalbuminuric patients, while they predominantly show mesangial expansion and tubulointerstitial and vascular changes. The prevalence of NA-DKD has been increasing during the past decade, with a wide range of prevalence in different studies. It seems that patients with NA-DKD are more likely to be female and have better metabolic profile including a lower Hb A1c, lower triglyceride, lower cholesterol, lower BMI and systolic blood pressure, and lower rate of retinopathy. Compared to patients with albuminuria, those with NA-DKD show a lower risk for progression to end-stage kidney disease (ESKD), or rapid decline in eGFR. They also have increased risks of death and hospitalization for heart failure compared with non-DKD diabetic patients, but a lower risk in comparison with albuminuric DKD, regardless of GFR. There is no effective treatment for this phenotype of the disease, but limited data support the use of SGLT2 inhibitors to slow chronic kidney disease progression along with appropriate metabolic risk factor control. More clinical research and pathologic studies are needed for a better understanding of the phenotype, prevention, and treatment methods of the disease. DOI: 10.52547/ijkd.7966